Penerapan PSAP 07 tentang Aset Tetap pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Palembang - Reghina Elvhira Khansa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the Application of Fixed Assets Accounting based on based on PSAP 07 at the Palembang City Regional Financial and Asset Management Agency. In this study utilizing subjective exploration strategies with essential information sources through meetings and documentation. After the information is acquired then given engaging examination strategies. The information source was acquired from the Palembang City Provincial Monetary Administration Office, the Territorial Resource Monetary Administration area. The exploration utilized an examining strategy, specifically purposive testing to ten examples as witnesses. Information triangulation as the legitimacy of exploration information. The consequences of this study show that the use of fixed resource bookkeeping at the Palembang City Provincial Monetary and Resource The board Organization is as per the Assertion of Government Bookkeeping Guidelines No. 07. For characterization, acknowledgment, estimation, valuation, end or removal, revelation, and devaluation of resources is as per existing guidelines.